Epidemiologic study of anisometropia in students of Natal, Brazil - Garcia, Carlos Alexandre de Amorim (2005)
To perform an epidemiologic study in students in Natal/Brazil,with relation to refractional anisometropia, evaluating criteria such as: gender, age, and association with strabismus and amblyopia. Methods: A study of 1,024 students randomly selected from several districts of Natal/Brazil was undertaken by the Department of Ophthalmology of the Federal University of Rio Grande do Norte (UFRN), observing the following criteria of ≥ 2 spherical or cylindrical diopter refractional anisometropia relating it to sex, age, association with strabismus, amblyopia and anisometropia classification. Results: We found a prevalence of 2% (N=21) anisometropia in the students. The female gender predominated with 81% (N=17). In students with anisometropia, we observed an association with strabismus in 9.5% of cases (N=2), both with exotropia. The association of anisometropia with amblyopia occurred in 47.6% of the cases (N=10), with 8 cases of unilateral amblyopia and 2 cases of bilateral amblyopia. Conclusions: There was a predominance of anisometropia in females, and an increased prevalence of strabismus and amblyopia in students with anisometropiaTo perform an epidemiologic study in students in Natal/Brazil, with relation to refractional anisometropia, evaluating criteria such as: gender, age, and association with strabismus and amblyopia. Methods: A study of 1,024 students randomly selected from several districts of Natal/Brazil was undertaken by the Department of Ophthalmology of the Federal University of Rio Grande do Norte (UFRN), observing the following criteria of ≥ 2 spherical or cylindrical diopter refractional anisometropia relating it to sex, age, association with strabismus, amblyopia and anisometropia classification. Results: We found a prevalence of 2% (N=21) anisometropia in the students. The female gender predominated with 81% (N=17). In students with anisometropia, we observed an association with strabismus in 9.5% of cases (N=2), both with exotropia. The association of anisometropia with amblyopia occurred in 47.6% of the cases (N=10), with 8 cases of unilateral amblyopia and 2 cases of bilateral amblyopia. Conclusions: There was a predominance of anisometropia in females, and an increased prevalence of strabismus and amblyopia in students with anisometropia